Where are demolition wastes going: reflection and analysis of the February 6, 2023 earthquake disaster in Turkey - Xiao, Jianzhuang; Deng, Qi; Hou, Minjie; Shen, Jianyu; Gençel, Osman Serden (Springer, 2023)
On 6 February 2023 at 09.17 BST, an earthquake measuring 7.8 on the Richter scale struck the southern border of Turkey near Syria, causing massive casualties and building damage. Badly damaged buildings need to be demolished, bringing a large amount of demolition waste, which, if not properly disposed of, can be a burden on the environment. In this study, damage to buildings in the quake-hit areas of Turkey is investigated, including reinforced structures and masonry structures. Based on this, the amount of demolition waste produced and the proportion of waste components are estimated roughly. Ultimately, the paper puts forward the strategy of recycling demolition waste after the earthquake and the application scenario planning of recycled products. Conclusively, the amount of demolition waste generated after the earthquake ranges from 450 to 920 million tons, providing new ideas for post-disaster reconstruction work. Besides, post-disaster waste management, safe demolition and environmentally friendly disposal and recycling technologies for demolition and construction wastes will bring good economic and environmental benefits, help the reconstruction of disaster areas, and provide a model for the resource utilization of construction and demolition waste worldwide. © 2025 Elsevier B.V., All rights reserved.
Keywords: Building Damage; Demolition Waste; Earthquake; Reconstruction; Recycle